Experience-focused Thinking and Cognitive Mapping in Ethical Banking Practices: From Practical Intuition to Theory - Ferreira, F.; Jalali, M.; Ferreira, J. (2016 GIKA International Conference, 2016)
Concern over ethical management and ethical principles in banking practices is rapidly increasing. The alignment of such concerns with daily operations, however, is often far from simple. Grounded on the knowledge and professional experience of a group of banking experts, this paper proposes the use of cognitive mapping to enhance our understanding of the key factors underlying ethical banking and the manner in which they inter-relate with each other. By providing a process for the integration and representation of a group of experts’ experience-focused thinking, such a cognitive map allows for the development of an empirically informed methodological framework. By depicting the cause-and-effect linkages among determinants of ethical banking, and allowing them to be analyzed from a holistic perspective, such a map not only serves as a support for the integration of values, ethics and banking, but can help create theory, based on experts’ practice in this field. The advantages and limitations of this proposal are presented and discussed.